Peran Komik Digital Mengenai Kepribadian Introvert Semangat Rani Lewat Kisah Karakter Utama Rani - Azhari A lmirana; Shienny Megawati (Jurnal Vicidi, 2022)
Every human being is born with different characteristics from one another. To find out these types of characteristics, psychologists from ancient times did various ways to continue to study them, such as taking an individual approach, namely through personality tests. One personality type that has been widely recognized is the extrovert and introvert personality. But unfortunately introverts don't get positive treatment like extroverts due to the characteristics of introverts who don't like interaction, causing a bad stigma in society to bring negative stereotypes. That's why there needs to be an interesting representation of introverts in order to slowly educate them. A digital comic project was designed called Semangat Rani which raised the topic of introverted personality through the daily narration of the main character Rani as an introvert's personal point of view while at the same time providing insight into the mascot in the comic, namely the background story to convey messages through storytelling in comic scenes so that readers can sympathize or connect directly also could be it own brand identity which is aimed at an audience in Indonesia with an age range from teenagers to young adults 15 – 25 years old through the social media Instagram. This study will use data collection methods from literature studies, interviews and surveys. The purpose of this research is to find out whether the content is effective or correct and its promotional media through the characterization of Rani's character as the mascot for Semangat Rani the comic with the hope that the design of the Semangat Rani the comic can slowly awaken awareness to the audience about introverts so that they can change the bad stigma that surrounds them all about this personality. Keywords: Introvert Personality, Character Design, Representation, Comic